Konsep Dasar dan Komponen Strategi Pembelajaran - Sofia Nadilah; Gusmaneli Gusmaneli (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Learning strategy is important in the process of implementing learning, without a learning strategy, the learning process will not be directed and learning objectives are difficult to achieve. In order for a learning process to be more directed, it is necessary to know the components of the learning strategy, which include learning objectives, learning materials, teachers as educators, students as learners, methods, tools, learning resources, and evaluation. Each component of learning complements each other. Each component is interrelated with one another, thus creating an effective, directed, and enjoyable learning process. By applying the right strategy, it is hoped that it will be able to improve the quality of learning and achieve learning objectives.